The Production of ACC Deaminase and Trehalose by the Plant Growth Promoting Bacterium Pseudomonas sp. UW4 Synergistically Protect Tomato Plants Against Salt Stress - Orozco-Mosqueda, Ma. del Carmen; Duan, Jin; DiBernardo, Mercedes; Zetter, Elizabeth; Campos-García, Jesús; Glick, Bernard R.; Santoyo, Gustavo (Frontiers in Microbiology, 2019)
Soil salinity is a major problem in agriculture. However, crop growth and productivity can be improved by the inoculation of plants with beneficial bacteria that promote plant growth under stress conditions such as high salinity. Here, we evaluated 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity and trehalose accumulation of the plant growth promoting bacterium Pseudomonas sp. UW4. Mutant strains (mutated at acdS, treS, or both) and a trehalose over-expressing strain (OxtreS) were constructed. The acdS mutant was ACC deaminase minus; the treS- strain significantly decreased its accumulation of trehalose, and the double mutant was affected in both characteristics. The OxtreS strain accumulated more trehalose than the wild-type strain UW4. Inoculating tomato plants subjected to salt stress with these strains significantly impacted root and shoot length, total dry weight, and chlorophyll content. The evaluated parameters in the single acdS and treS mutants were impaired. The double acdS/treS mutant was negatively affected to a greater extent than the single-gene mutants, suggesting a synergistic action of these activities in the protection of plants against salt stress. Finally, the OxtreS overproducing strain protected tomato plants to a greater extent under stress conditions than the wild-type strain. Taken together, these results a consistent with the synergistic action of ACC deaminase and trehalose in Pseudomonas sp. UW4 in the protection of tomato plants against salt stress.